2012
DOI: 10.1021/ie201872v
|View full text |Cite
|
Sign up to set email alerts
|

Immiscible Foam for Enhancing Oil Recovery: Bulk and Porous Media Experiments

Abstract: This paper reports a laboratory study of foams intended to improve immiscible gas flooding in oil production. The study is relevant for both continuous and water alternating gas (WAG) injection schemes. The effect of oil on the longevity of nitrogen and air foams was studied in bulk for a selected set of surfactants. Foam heights were measured in a glass column as a function of time, in the absence and presence of mineral and crude oils. The column experiments indicated that foam longevity increases as the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(75 citation statements)
references
References 44 publications
4
71
0
Order By: Relevance
“…Others, however, have shown that stable foams can be generated in the presence of oil if an appropriate foaming agent is selected [22,26,27]. It has also been demonstrated that foam can be generated effectively in the presence of heavy oil [28,29]. Indeed, there are other experiments that suggest that oil can improve the stability of foam.…”
Section: Introductionmentioning
confidence: 99%
“…Others, however, have shown that stable foams can be generated in the presence of oil if an appropriate foaming agent is selected [22,26,27]. It has also been demonstrated that foam can be generated effectively in the presence of heavy oil [28,29]. Indeed, there are other experiments that suggest that oil can improve the stability of foam.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the surfactants molecules demote the gas/ liquid interfacial tension and thereby contribute to the formation of small bubbles. [14] Foam Application in Enhanced Oil Recovery Immiscible gas injection can potentially increase the recovered oil from the reservoir, but one of the main drawbacks that is associated with immiscible gas injection processes is the gas segregation and fingering through the high permeability region in the reservoir. [15][16][17] These phenomena are due to a large contrast between the viscosity and density of gas compared to oil.…”
Section: General Aspectsmentioning
confidence: 99%
“…Also they showed that oil recovery and pressure drop across the core increased when the stability of the foam increases. Andrianov et al, [14] through a series of bulk experiments, showed that foam stability depends on the oil and surfactant molecules carbon chain length. They reported that oils with a higher carbon number affect foam stability less than those with a lower carbon number.…”
Section: General Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been successfully utilized in a large variety of emerging fields recently, such as blast mitigation [1], an intermediate structure to produce porous materials [2][3][4] and scaffolds for tissue engineering [5,6], in addition to the traditional applications of froth flotation [7], cosmetics [8], and enhancing oil recovery [9]. Although these applications are reliant upon stable foam in general, foam is a thermodynamically unstable system on account of high gas-liquid interface area.…”
Section: Introductionmentioning
confidence: 99%